Mexico, Indonesia, South Korea, Turkey, and Australia (MIKTA): Middle, Regional, and Constructive Powers Providing Global Governance. Issue 3 (24th August 2016) - Schiavon, Jorge A.; Domínguez, Diego
Abstract: This paper argues that MIKTA (Mexico, Indonesia, South Korea, Turkey, and Australia) are middle, regional, and constructive powers that can serve as providers of global governance in the international system. In order to support this idea, the paper first reviews the literature on these concepts, arguing that they can be complementary. Then, it explains why the MIKTA countries can be defined as middle, regional and constructive powers. To do so, it describes what MIKTA is, as well the common characteristics, objectives, and strategies that the countries that compose this mechanism share. Finally, it argues that in order for MIKTA countries to serve as middle, regional, and constructive powers, they need to consolidate the support of all relevant State and non‐State actors in their countries, allowing MIKTA to become a relevant mechanism to promote and generate public goods in the international system, specially global governance.